2017
DOI: 10.1007/s13593-017-0448-4
|View full text |Cite
|
Sign up to set email alerts
|

First formulation of a botanical active substance extracted from neem cell culture for controlling the armyworm

Abstract: Neem (Azadirachta indica) produces several of compounds known as limonoids, which have an antifeedant effect on insects. These compounds are extremely sensitive to some environmental factors that cause their degradation. Despite this, they are widely used in many formulations of commercial bioinsecticides. We evaluated the photodegradation of the crude extract from A. indica cell culture and designed the formulation of a botanical active substance for controlling insects. The crude extract was subjected to 368… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…The most common destabilization phenomenon like occulation, creaming, and coalescence etc. are directly related to droplet size 25,26 . The small size of nanoemulsion is desirable in achieving optimal e ciency.…”
Section: Role Of Prosopis Juli Ora On Droplet Size Poly Dispersive Imentioning
confidence: 99%
“…The most common destabilization phenomenon like occulation, creaming, and coalescence etc. are directly related to droplet size 25,26 . The small size of nanoemulsion is desirable in achieving optimal e ciency.…”
Section: Role Of Prosopis Juli Ora On Droplet Size Poly Dispersive Imentioning
confidence: 99%
“…Previous research has shown that azadirachtin has a variety of biological effects on insects, such as antifeeding (Tomé et al, 2013), inhibition of growth and development (Lucantoni et al, 2006), avoidance (Bezzar-Bendjazia, Kilani-Morakchi, Maroua, & Aribi, 2017;Liu & Liu, 2006), cytotoxicity (Radhika, Sahayaraj, Senthil-Nathan, & Hunter, 2018), and so on. The antifeedant index and the affected leaf area of corn infected with Spodoptera frugiperda were evaluated by a laboratory and field bioassay by Zuleta-Castro, Rios, Hoyos, and Orozco-S nchez (2017). The results showed that the crude extract of azadirachta had good stability and an antifeedant effect.…”
mentioning
confidence: 99%
“…One video described the production and use of a bio-pesticide using Neem and hot pepper. Neem (Azadirachta indica) produces several of compounds known as limonoids, which have an antifeedant effect on insects and are therefore used in the formulation of many commercial biosinsecticides [41]. A second video compared three different ways of applying compost: uniformly, in rows, and in pockets.…”
Section: Methodsmentioning
confidence: 99%